Environmental Factors and Bank Performance: How Financial Market Role Players React in Malaysia? - Rosa, Ade Tutty Rokhayati; Fauzi, Ikka Kartika Abbas; Sanusi, Zuraidah Mohd (International Journal of Energy Economics and Policy, 2020)
This study is applied in the region of Malaysia with a prime objective to investigate whether environmental performance indicators are impacting on banking sector performance during the period 2014-2018. For this purpose, this study has considered a sample of 6 Malaysian banking firms working under the regulator of Bank Nagara Malaysia. considering the both dimension of time series and cross section, three panel models known as simple regression, fixed and random effect are statistically applied. However, correlation matrix between the variables is also presented for the better understanding. Findings through panel model shows that Eco. System vitality is adversely affecting the EBIT, in all three models, whereas environmental health is a negative indicator of EBIT. for EAT, eco system vitality is again providing the evidence for adverse influence during the study period. In addition, black carbon emission intensity is causing a decline in EAT in both simple regression and fixed effect estimator. For ZROE, environmental health, eco system vitality are negative while carbon emission intensity is positive sign. For the last indicator of banking sector performance, it is found that eco. System vitality is a negative sign causing a decline in ZROA during 2014-2018. it is suggested that there is a strong need to control the adverse impact of some of the environmental factors on the banking industry of Malaysia, where different public sector departments are held responsible. For the future studies, this study suggest considering all the banking firms, long data period and other regional economies. Keywords: environmental factors, climate change, banks, Malaysia JEL Classifications: Q19, E5 DOI: https://doi.org/10.32479/ijeep.10694